PEMANFAATAN MEDIA SOSIAL DALAM PEMBELAJARAN BAHASA MANDARIN OLEH MAHASISWA PENDIDIKAN BAHASA MANDARIN UNIVERSITAS NEGERI JAKARTA - Marlen, Karyn Olivia; Wardhani, Rizky; Aditya, Rendy (Universitas Negeri Surabaya, 2025)
This research examines social media, which is a digital platform that provides various facilities for social activities, such as communicating or sharing content in the form of videos or photos. This research is motivated by the large number of social media that promote online Mandarin learning or provide knowledge related to Mandarin for free. So it needs to be studied to find out whether the use of social media can be beneficial in terms of enriching vocabulary, improving four Mandarin language skills, or other benefits. This research uses quantitative methods. The data collection technique in this research uses survey techniques via questionnaires. The results of this research show that many students use Instagram as a medium for learning Mandarin. Apart from that, students also mentioned that Instagram has many benefits in helping students' learning process. The conclusion is that Instagram media is widely used by respondents to help students learn Mandarin, because Instagram has many very useful features, which makes students interested in learning Mandarin using Instagram.